Determining Total Phenolics, Anthocyanin Content and Ascorbic Acid Content in Some Plum Genotypes Grown in Ardahan Ecological Conditions - Z. T. ABACI; E. MARTİN; E. SEVİNDİK; O. KAYGUSUZ; A. ERMİŞ (International Journal of Secondary Metabolite)
In this study, total phenol content, total anthocyanin content, brix, pH, titrable acidity and total ascorbic acid content in the five plum genotypes cultivated in Ardahan City are determined and sustenance of the plums are revealed. Total phenol content was determined with folin-ciocalteu’s method, total anthocyanin content was determined with pH differential method and total ascorbic acid was determined with 2,6-dichlorophenolindophenol method.It is detected that the genotype with the highest brix content (%13.9) and lowest acidity (%0.98) is cancur, the genotype with the lowest brix content (%11) and highest acidity (%2.06) is wild plum, the genotype with the highest content of total anthocyanin, total phenolic substance and ascorbic acid is the wild plum and the genotype with the least content of these is the water plum. As a result of the study, it is revealed that the plum fruit has high levels of phenolic substance, anthocyanin and ascorbic acid content, so it has a high sustenance.